2019
DOI: 10.1002/jlb.3mir1118-434r
|View full text |Cite
|
Sign up to set email alerts
|

Detecting lipopolysaccharide in the cytosol of mammalian cells: Lessons from MD-2/TLR4

Abstract: Proinflammatory immune responses to Gram-negative bacterial lipopolysaccharides (LPS) are crucial to innate host defenses but can also contribute to pathology. How host cells sensitively detect structural features of LPS was a mystery for years, especially given that a portion of the molecule essential for its potent proinflammatory properties-lipid A-is buried in the bacterial membrane. Studies of responses to extracellular and vacuolar LPS revealed a crucial role for accessory proteins that specifically bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 70 publications
0
12
0
Order By: Relevance
“…Such interpretation would be in line with a recent study showing that caspase-4 recognizes LPS-rich membrane interfaces. According to this study, caspase-4 could bind directly to LPS-rich OMVs formed by N. meningitidis as well as to the high molecular mass aggregates of purified metabolically radiolabeled LPS (172)(173)(174). Indeed, it has been demonstrated that purified caspase-4 (C258A) and CARD domain from E. coli could bind huge LPS micelles and disaggregate them to small complexes in vitro (175).…”
Section: Zamyatina and Heinementioning
confidence: 83%
“…Such interpretation would be in line with a recent study showing that caspase-4 recognizes LPS-rich membrane interfaces. According to this study, caspase-4 could bind directly to LPS-rich OMVs formed by N. meningitidis as well as to the high molecular mass aggregates of purified metabolically radiolabeled LPS (172)(173)(174). Indeed, it has been demonstrated that purified caspase-4 (C258A) and CARD domain from E. coli could bind huge LPS micelles and disaggregate them to small complexes in vitro (175).…”
Section: Zamyatina and Heinementioning
confidence: 83%
“…Activation of LPS-sensing cytosolic caspases by LPS also appears to depend upon the acylation state of LPS (36)(37)(38). An effect of AOAH-dependent LPS deacylation on regulating the activation of this cytosolic recognition/response system has not been reported.…”
Section: From Stimulus To Inhibitor: the Importance Of Lps Acylationmentioning
confidence: 99%
“…It has recently been established that TLR4 is also involved in so-called canonical activation of the NRLP3 inflammasome. The LPS-induced activation of this inflammasome via the canonical and also via a non-canonical, hence not involving TLR4, pathways has been intensively studied and discussed in excellent reviews [105][106][107][108]. In brief, the NLRP3 inflammasome is a multimeric complex of NRLP3, ASC, NEK7 and pro-caspase-1, which ultimately serves to promote autoproteolysis and activation of caspase-1.…”
Section: Signaling Pathways Triggered By Tlr4mentioning
confidence: 99%